Is Freedom Enough? An Exploratory Case Study on the Links Between Liberation Management and Self-Determination Theory - Jacques-Gagnon, Chantale (Université d'Ottawa / University of Ottawa, 2022)
This case study looks at the lived experiences of workers, within a manufacturing plant in southern Quebec, undergoing a liberation management transformation. Using the qualitative approach, semi-directed interviews were held as well as non-participant observation and documentation analysis. In total, 18 people were interviewed, recruited on a voluntary basis, and coming from different sectors of the business with a diversity in age, experience and gender. The data collected allowed for a deeper understanding of the advantages, obstacles, expectations, and limitations faced by the workers and the management team (known as coaches). The liberation transformation was not an easy road but one that enabled workers to experience a sense of freedom, purpose and belonging. Using Self-Determination as a theoretical lens, it was clear that all three components of the theory (autonomy, competency and relatedness) were at the heart of the liberation process, yet a gap remained to grasp the complexity of the transformation. The paradox perspective was mobilized to enrich the understanding of the phenomena and inspired the design of a conceptual model. Well-being and financial performance are seen as by-products of this type of organizational form which makes its study even more relevant. Practitioners can benefit from a liberation process, yet this type of culture requires a major mental shift, including unlearning behaviors, solid communication, trusting relationships and ongoing training, especially in soft skills, to ensure a smoother transition from traditional management practices. Freedom is one part of the liberation process, but it is not enough in itself. An ability to embrace the paradoxes of freedom and the tensions it generates is fundamental. Finally, trust needs to remain at the core of the initiative, otherwise the risk of manipulation is inherent.
Keywords: Liberation management; Enteprise libérée; Self-Determination Theory; Théorie de l'autodétermination; Freedom Form; Horizontal Leadership